The Use of AI as a Personalized Correction Tool to Improve Students’ Writing Skill - Aripuspita, Luh Mega; Dewi, Kadek Sintya; Pratiwi, Ni Putu Astiti (Universitas Pahlawan Tuanku Tambusai, 2026)
As education continues to adapt in the digital era, technology plays a central role in supporting learning processes. In EFL instruction, writing remains a challenging skill as many learners are still facing difficulties in producing accurate, coherent, and well-structured texts despite the availability of various technological tools. Responding to this situation, this study aims to utilize AI, specifically ChatGPT as a personalized correction tool to improve the writing skills of ninth-grade students at SMP Negeri 1 Kubutambahan. A Classroom Action Research design was conducted in two cycles involving 31 students. Data were gathered through pre-test, post-test I, and post-test II including writing assessments, questionnaires, and semi-structured interviews. The results showed significant improvement in students’ writing with the mean score increasing from 68 in the pre-test to 79.7 in Cycle I and 82.8 in Cycle II. Students exhibited progress in grammar, vocabulary development, and text organization, alongside positive perceptions toward ChatGPT usage with increasing scores from 4.05 to 4.28. Overall, the study concludes that incorporating ChatGPT as AI-assisted feedback into writing instruction can effectively improve students’ writing skill while supporting autonomy and self-directed learning.